2022
DOI: 10.1111/are.16059
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of optimum dietary protein requirement for maximum growth of common carp ( Cyprinus carpio ) fingerlings

Abstract: A 90‐day feeding trial was carried out to investigate the effect of varying dietary protein on growth performance, health status, intestinal enzyme activity, carcass composition and intestinal histomorphology of common carp (Cyprinus carpio) fingerlings for defining the optimum dietary protein. Five groups were fed with different crude protein content: T1 (36%), T2 (38%), T3 (40%), T4 (42%) and T5 (44%). Each group was run in triplicate with 10 fingerlings per tank. The group fed with 38% crude protein showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Similar problems were researched in other studies (Shipton, et al, 2022;Al-Jader, et al, 2012;Fan, et al, 2015;Nandeesha, et al, 2000). The effects of feeding frequency on carp weight gain are presented in the work of Ali, et al, (2022). The nutritional value of cereals in the diet of Common carp is the topic addressed by the authors Sultana et al, (2001), considering that the local production of quality feeder can bring considerable benefits to the fish farming industry.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Similar problems were researched in other studies (Shipton, et al, 2022;Al-Jader, et al, 2012;Fan, et al, 2015;Nandeesha, et al, 2000). The effects of feeding frequency on carp weight gain are presented in the work of Ali, et al, (2022). The nutritional value of cereals in the diet of Common carp is the topic addressed by the authors Sultana et al, (2001), considering that the local production of quality feeder can bring considerable benefits to the fish farming industry.…”
Section: Introductionmentioning
confidence: 68%
“…The problem of finding optimal diets for Israeli carp is presented in the paper of Zahra, et al, (2015) finally recommending a percentage of 40% proteins with 14% lipids. A research done by Ali et al, (2022) present the results of preliminary research on the optimal diet of carp. Since for the client the quality of the fish meat is highly important, the problem of the fish diet is also researched by the authors Ljubojević, et al, (2022), who give several feeding recipes, including for carp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this trend, our results affirmed that fish that were fed every other day did not differ from those fed every day in SGR, but they had the best FCR. Data from many previous study stated that alternated-day feeding is a vital tool to improve growth rate of fish as a result of reduced feed waste either through more complete consumption or improved nutrient absorption [ 23 ]. Confirmation of our observations, Bolivar et al [ 24 ] found that fish fed daily had higher growth but did not significantly differ with those fed alternate-day feeding (EOD), they reported that a significantly better FCR was obtained for fish fed EOD or on alternate days than for fish fed daily.…”
Section: Discussionmentioning
confidence: 99%
“…While dietary protein is important for fish growth and survival, it also accounts for a large proportion of total feed costs (Kabir et al, 2019). Up to the optimal level, dietary protein intake can improve fish growth (Zhang et al, 2017;Sivaramakrishnan et al, 2022); however, excess dietary protein is catabolized for energy production, increasing feed costs, and affecting water quality via nitrogen (ammonia) excretion (Ali and Rawal, 2022;Peres et al, 2022).…”
Section: Introductionmentioning
confidence: 99%